Regulation of T cell afferent lymphatic migration by targeting LTβR-mediated non-classical NFκB signaling - Wenji Piao (Nature Portfolio, 2018)
Lymphotoxin beta receptor (LTβR) signalling regulates leukocyte migration through the lymphatic endothelial layers. Here, the authors show that treatment of an LTβR-derived decoy peptide can target the non-classical NFκB pathway to inhibit T cell and dendritic cell migration and ameliorate contact hypersensitivity in mouse models.